Effect of different structured TiO2 particle on anticorrosion properties of waterborne epoxy coatings. (3rd July 2016) - Wang, N.; Fu, W.; Sun, M.; Zhang, J.; Fang, Q.
Abstract : Anticorrosion properties of waterborne epoxy coatings with three structured nano-particles of TiO2 were investigated and compared. The surface morphology and structure of TiO2 have been analysed by XRD, SEM and N2 adsorption–desorption. Corrosion performance of the nano-composite coating was investigated employing electrochemical impedance spectroscopy and salt spray test. Coatings with mesoporous TiO2 (meso-TiO2 ) possessed the best corrosion performance among the coating specimens. The EIS results show that the resistance value of coating with meso-TiO2 was above 5.4 × 10 8  Ω cm 2 which was higher than the other nano-composite coatings. Possible strong interactions between polymeric matrix and meso-TiO2 caused high barrier properties.